Early-Stage Vision and Perceptual Imagery in Autism Spectrum Conditions - Maróthi, Rebeka; Csigó, Katalin; Kéri, Szabolcs (Frontiers in Human Neuroscience, 2019)
Autism spectrum disorders (ASD) are characterized by multifaceted alterations in visual perception and mental imagery. However, the interaction between early-stage visual perception and imagery has not been explored. We recruited 40 individuals with ASD and 20 healthy control subjects to participate in a lateral masking task. We asked the volunteers to detect a luminance-contrast target pattern (Gabor patch) flanked by two collinear masks. The flanking masks inhibit target detection at small target-mask distances and facilitate target detection at intermediate target-mask distances. In the perceptual task, the masks appeared adjacent to the target. In the imagery task, participants imagined the masks immediately after seeing them. Results revealed that ASD individuals with exceptional visuoconstructional abilities (enhanced Block Design performance) (n = 20) showed weaker inhibition at small target-mask distances and stronger facilitation at intermediate target-mask distances relative to the control subjects. In other words, they detected that target at lower contrast thresholds compared to the control subjects. Visual imagery was markedly dampened in ASD regardless of the visuoconstructional abilities. At the behavioral level, these results indicate increased perceptual facilitation via lateral neuronal connections in the primary visual cortex of ASD individuals with exceptional visuoconstructional abilities, together with less efficient mental imagery.